pERK-dependent defective TCR-mediated activation of CD4(+) T cells in end-stage renal disease patients - Huang, Ling (Immun Ageing, 2017)
BACKGROUND: Patients with end-stage renal disease (ESRD) have an impaired immune response with a prematurely aged T-cell system. Mitogen-activated protein kinases (MAPKs) including extracellular signal-regulated kinase (ERK) and p38, regulate diverse cellular programs by transferring extracellular signals into an intracellular response. T cell receptor (TCR)-induced phosphorylation of ERK (pERK) may show an age-associated decline, which can be reversed by inhibiting dual specific phosphatase (DUSP) 6, a cytoplasmic phosphatase with substrate specificity to dephosphorylate pERK. The aim of this study was to assess whether ESRD affects TCR-mediated signaling and explore possibilities for intervening in ESRD-associated defective T-cell mediated immunity. RESULTS: An age-associated decline in TCR-induced pERK-levels was observed in the different CD4(+) (P < 0.05), but not CD8(+), T-cell subsets from healthy individuals (HI). Interestingly, pERK-levels of CD4(+) T-cell subsets from young ESRD patients were in between young and elderly HI. A differentiation-associated decline in TCR-induced ERK and p38 phosphorylation was observed in T cells, although TCR-induced p38 phosphorylation was not significantly affected by age and/or ESRD. Frequencies of TCR-induced CD69-expressing CD4(+) T cells declined with age and were positively associated with pERK. In addition, an age-associated tendency of increased expression of DUSP6 was observed in CD4(+) T cells of HI and DUSP6 expression in young ESRD patients was similar to old HI. Inhibition of DUSP6 significantly increased TCR-induced pERK-levels of CD4(+) T cells in young and elderly ESRD patients, and elderly HI. CONCLUSIONS: TCR-mediated phosphorylation of ERK is affected in young ESRD patients consistent with the concept of premature immunological T cell ageing. Inhibition of DUSP6 specific for pERK might be a potential intervention enhancing T-cell mediated immunity in ESRD patients. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12979-017-0096-1) contains supplementary material, which is available to authorized users.